PENGARUH PENDIDIKAN GRATIS TERHADAP EFEKTIVITAS KINERJA GURU PADA SMK NEGERI 1 PATTALLASSANG DI KABUPATEN GOWA - Yahya, Abdul Azis; Maldun, Syamsuddin; Chakti, Andi Gunawan Ratu (Siddiq Institute, 2023)
Singer study aims to review the effectiveness of costs kos know the description of teachers of SMK Negeri 1 Pattallassang And Achievement Level Overview Students learn SMK Negeri 1 Pattallassang well as the influence of free education teacher Against effectiveness boarding costs AT SMK Negeri1 Pattallassang in Gowa. Singer Research research using quantitative descriptive with population is Entire Class X and XI That amounts to 270 students. Given Timeframe Relative population is big and can be researched not all that is necessary to review a sample of a population determine the with cluster sampling method, the sample is determined based on a sample table Krejie Dan Morgan is 159 students. Data collection was conducted with way using questionnaires, observation, and documentation. Data analysis techniques used That is the descriptive statistical analysis using with mean (average) and standard deviation, and inferential statistical analysis WITH using simple linear regression to test the hypothesis review. Research results show that free education on SMK Negeri 1 Pattallassang Gowa hearts belong to either category, viewed from free education aspects These include: service and convenience, Assurance Education, and Education bermutu. kinerj teacher effectiveness at SMK Negeri 1 Pattallassang Gowa classified category Very Good hearts are reviewed From Lesson Planning, Learning Process, and Learning Evaluation. While the learning achievement of students classified as High View of aspect terms of cognitive, affective and psychomotor student. Further influences of significant Sufficient free Education Against teacher effectiveness boarding costs at SMK Negeri 1 Pattallassang Gowa 53.7 percent.